KEWENANGAN JAKSA PENUNTUT UMUM DALAM MELAKUKAN UPAYA HUKUM PENINJAUAN KEMBALI DALAM PERKARA PIDANA - Hendrawan, Dady (The Juris, 2017)
The Prosecutor on behalf of the state for the sake of the public is entitled to file a judicial review law although the Criminal Procedure Code does not regulate it, but in practice the Prosecutor is allowed to conduct a judicial review, when it concerns the general interests. The filing of this Repeater legal remedy as a legal breakthrough to break through legalistic, as the principles of legislation in Indonesia under existing regulation.